PEMBELAJARAN DENGAN PENGGUNAAN MEDIA PADA RENANG GAYA DADA MAHASISWA PJKR ANGKATAN 2013 DI STKIP PASUNDAN CIMAHI - Pristiawati, Ani (STKIP Pasundan, 2016)
The purpose of this study was to determine the differences in learning media for breaststroke swimming skills in swimming. The sample of this study consisted of 39 students majoring in Health and Recreation Physical Education, at STKIP Pasundan Cimahi. This research is an action research using a cycle consisting of planning, action, observation, evaluation and reflection. And the media used are noodle swimming and 1500 ml bottles. The results showed that (1) Overall the use of media was very helpful in learning to develop methods for breaststroke swimming skills. (2) There is an increase from cycle 1 to cycle 2 breaststroke swimming skills. (3) The use of noodle swimming and 1500 ml bottles, was successful because of increased breaststroke swimming skills. (4) The lack of learning media, can help add insight and methods of learning chest swimming